Effects of urbanization on the structure of plant-flower visitor network at the local and landscape levels in the northern Argentinian Yungas forest - Amado De Santis, Alejandro A.; Lomáscolo, Silvia B.; Chacoff, Natacha P. (Frontiers in Sustainable Cities, 2023)
Human population and cities are growing fast, with a concomitant modification of the land surface. Urbanization is driving biodiversity loss and biological homogenization, which impacts human well-being. In this study we evaluated the influence of urbanization on flower visitor assemblage using an interaction network approach. We assesed the effect of different variables at the local and landscape scales on community parameters and network metrics along a gradient of urbanization located in a subtropical montane Yungas forest. We found that local variables affected richness of flower visitors, that is, flower visitor frequency increased with greater flower coverage, high stability of floral resources and the proportion of exotic plants. Moreover, local variables affected the Shannon diversity index and also the nestedness (NODF) and the specialization (H2) indexes. Landscape variables such as altitude and proportion of impervious surface (a proxy of urbanization) affected both richness of flower visitors and H2. The effect of intensifying urbanization over the richness of flower visitor differs across the altitudinal gradient, with higher potential impact on flower visitors in urban developments at higher than lower altitudes. In conclusion, our results indicate that local and landscape variables affect community parameters and structure of plant-flower visitor networks to different extents and strength.